HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU KESELAMATAN DIRI TERHADAP BAHAYA DI LINGKUNGAN SEKOLAH PADA MURID KELAS IV-VI SEKOLAH DASAR NO 40/III KOTO MAJIDIN KABUPATEN KERINCI - Wenny Murdina Asih; Dara Lita Febiola (Ensiklopedia of Journal, 2021)
Lack of students’ knowledge about personal safety in school environment which can endanger their own safety is the cause of accidents at school. The purpose of this research was to determine the Relationship between Knowledge Level and Personal Safety Behavior Against Danger in School Environment at Class IV-VI Students of Elementary School No. 40 / III Koto Majidin, Kerinci Regency. This research was quantitative observational by using analytic survey with a cross sectional approach. This research was conducted on September 2020 - February 2021. The object of this research was all students in grades IV, V, VI with total number of students were 77 students. The instrumentation used as a data collection was questionnaire. The data obtained were processed by using SPSS software, analyzed univariately and bivariately using the Chi-Square test. The results showed that students who had a high level of knowledge were 58.4%, and students with positive self-safety behavior were 55.8%. The results of statistical tests showed that there is a relationship between Knowledge Level and Personal Safety Behavior Against Danger in the School Environment at Class IV-VI Students of Elementary School No 40 / III Koto Majidin, Kerinci Regency. It is hoped that the school can implement a personal safety behavior program in the form of providing materials and practices for local content subject to students at least 1-2 times a month.